Religion, Illness Perception and Coping in Pandemics: A Systematic Review - Yap, Chee-Khong (Research in the social scientific study of religion, 2022)
Religious community is a cultural system that embodies specific interpretation of illnesses and healing signs. Ignoring its influence on epidemic perception and coping has been a cultural myopia in current psychological science. Therefore, this paper set out to conduct systematic review on the past psychological studies on how different religious believers perceived and coped with a pandemic. A rigorous literature search using PRISMA guidelines on EBSCOHost, Ovid, and PubMed databases was conducted. Any empirical studies that were published in 2000-2020 which contained participants from certain religious groups, and constructs that fell under "illness perception" and/or "coping strategies" within a human pandemic context were included. From the originally generated 12,438 references, after cleaning, screening and quality evaluation, 17 quality papers remained for critical analysis. Due to the timeframe of the selected papers, most of the studies revolved around HIV/AIDS as an epidemic in the American and African continents. Only three major religious traditions were identified - Christianity, Islam, and Buddhism. Themes of research findings were extracted through thematic analysis and consensus coding.